Impact of environmental factors on the dietary preferences of Salmophasia bacaila in the Dhepa River, Bangladesh - Hossain, Md. Afzal; Yesmin, Most. Sabina; Aktar, Shefali; Mamun, Md.; Roy, Krishna Chandra; Alam, Md. Ashraful; Haque, Md. Rezoanul (Journal of Fisheries, 2025)
This study investigates the environmental variability and gut contents of an indigenous fish chela (Salmophasia bacaila) in the Dhepa River, Bangladesh. We conducted fish sampling and measured water quality across three sites from September 2017 to February 2018. The results revealed significant fluctuations in water temperature, dissolved oxygen, and pH (PERMANOVA: p = 0.001). There was spatio-temporal variation in water transparency (PERMANOVA: p = 0.001). The prey analysis identified 13 prey groups in the diet of fish, predominantly consisting of phytoplankton (92.9%), while zooplankton contributed only 7.1%. Twenty phytoplankton and seven zooplankton genera were recorded in the guts, with significant temporal variations in prey diversity (PERMANOVA: p = 0.010). These findings highlight that S. bacaila are primarily plankton feeders, with shifts in prey diversity driven by environmental factors in the Dhepa River. This research enhances our understanding of ecological dynamics and the relationship between S. bacaila and their prey in riverine ecosystems.